Albert Calmette
Photograph of Albert Calmette, who was involved in immunological research to prevent tuberculosis infection and was the first to introduce active immunization against tuberculosis. He was a pupil of Louis Pasteur. "Triangle Volume VI No. 2 July 1963" appears at head of sheet.